Population structure of the glasshouse whitefly Trialeurodes vaporariorum (Hemiptera: Aleyrodidae) shows multiple introductions to the U.K. (29th October 2018) - Kareem, Ali A.; Port, Gordon; Wolff, Kirsten
Abstract: Whiteflies are major pests of many crops worldwide. Trialeurodes vaporariorum was introduced into the U.K. approximately 160 years ago. In the present study, we aimed to understand their genetic diversity and population structure and thus their invasion history. Mitochondrial CO1 sequencing showed that T. vaporariorum had a low level of variation. Microsatellite analysis showed a high diversity and indicated the presence 2, 6 and 10 clusters, which were, to a limited extent, linked to locations but not to host plants. The primary symbiont Portiera aleyrodidarum was detected in both sexes of T. vaporariorum, whereas only one secondary symbiont Arsenophonus sp. was detected in almost all females but not males. The population structure suggested that glasshouse agroecosystems restricted gene flow between glasshouse whitefly populations and that the movement of glasshouse whitefly was linked to human‐assisted spread. Taken together, the results of the present study suggest multiple but limited numbers of introductions of T. vaporariorum, mainly from countries nearest to U.K.